Ответы 2

  • (x+7)^2-(x-4)(x+4)=65 x^2+14x+49−x^2−4x+4x+16=18x+65−4x=14x+6514x+65=6514x=0x=0
    • Автор:

      raúlwwmi
    • 5 лет назад
    • 0
  • Решение:(х + 7)² - (х - 4)·(х + 4) = 65х² + 14х + 49 - (х² - 16) = 65х² + 14х + 49 - х² + 16 = 6514х + 49 + 16 = 6514х = - 49 - 16 + 6514 х = 0х = 0 : 14х = 0Ответ: 0.Проверка: (0 + 7)²- (0 - 4)·(0 + 4) = 65                    49 - (-16) = 65 - верно
    • Автор:

      tonibawy
    • 5 лет назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years